Economic corridors and regional development the Malaysian experience. - Athukorala, Prema Chandra (Economic working paper., 2017)
What are the prerequisites for a successful interregional economic corridor development program in a country with a federal system of government. This paper addresses this issue through an in depth study of the design, implementation, and the developmental impact of the Northern Corridor Economic Region in Malaysia, which encompasses the states of Penang, Kedah, Perlis, and Perak. It argues that, in addition to economic prerequisites, an adequately equipped suprastate institution with the operational flexibility to align individual states interests, and command compliance from all stakeholders is required to achieve the overarching goal of shared regional growth.